Orbital Bi-Stripes in High Doped Bilayer Manganites - Beale, T; Spencer, P; Hatton, P; Wilkins, S; Zimmermann, M; Brown, S; Prabhakaran, D; Boothroyd, A (2004)
We present high resolution high energy and resonant x-ray diffraction results from La2-2xSr1+2xMn2O7 for x=0.55,0.575 and 0.60. These compounds show superlattice reflections at wavevectors of (h+-δ,k+-δ,l) and (h+-2δ,k+-2δ,l), arising from orbital ordering with associated Jahn-Teller distortions and charge ordering respectively. We observe a phase transition between the x=0.55 and x=0.575 doping levels. Samples with x=0.55 display structural characteristics similar to those previously reported for x=0.5. Compared to this, the long range order in samples with x=0.55 and x=0.6 have a distinct change in wavevector and correlation. We attribute this to a new orbital bi-stripe phase, accompanied by weak, frustrated, charge ordering. The observed azimuthal dependence of the orbital order reflections supports the model proposed for this new phase.